1978
DOI: 10.1111/j.1095-8339.1978.tb01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical taxonomic studies on Solanum L. section Solanum (Maurella)

Abstract: Population differentiation was studied in 32 accessions belonging to Solanum L. section Solanurn (Maurella); these accessions represented 20 species of four differing ploidy levels. A study of discordance demonstrated that the species exhibit considerable inherent discordant variation; it also provided an estimate of the relative variabilities of characters within these populations, and the consistency with which they differentiate populations.Hierarchic clusters, obtained using the singlelink cluster method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 11 publications
1
49
0
Order By: Relevance
“…At the species level this is in line with other studies where morphological data have been used (e.g. Edmonds 1979b;Symon 1981;Edmonds and Chweya 1997;Henderson 1974) and with respect to S. nigrum and S. scabrum our results are similar to those of Dehmer (2001), Dehmer and Hammer (2004) and (Olet 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At the species level this is in line with other studies where morphological data have been used (e.g. Edmonds 1979b;Symon 1981;Edmonds and Chweya 1997;Henderson 1974) and with respect to S. nigrum and S. scabrum our results are similar to those of Dehmer (2001), Dehmer and Hammer (2004) and (Olet 2004).…”
Section: Discussionsupporting
confidence: 93%
“…This points to the possibility that under cultivation genetic changes are slowed down because both competition and natural selection are reduced, since environmental conditions are kept at an optimum and pests are artificially controlled. Edmonds (1979b) concluded that members of section Solanum are predominantly self-pollinating though natural and cross-breeding takes place. The vast variations shown by individuals of the same accession of S. scabrum and S. nigrum in the present study is not in line with Edmonds' conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic complexity of the large and variable group of species associated with the section Solanum is generally accepted (Edmonds 1979;Dehmer 2001). In the AFLP analysis, the S. mammosum taxa appear close to S. nigrum within the section Solanum, which does not support the inclusion of S. mammosum in the section Acanthophora, subgenus Leptostemonum, as was previously reported (Nee 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Further, genetic data show intermixing between S. scabrum and S. nigrum in some instances. Edmonds (1979) indicated that the intermixing of Solanum genotypes, irrespective of geographic locality points to the predominantly autogamous nature of members. S. scabrum subsp.…”
Section: Aflp Analysismentioning
confidence: 99%